Chemically tuned, bi-functional polar interlayer for TiO2 photoanodes in fibre-shaped dye-sensitized solar cells. Issue 5 (13th January 2020) - Ardhi, Ryanda Enggar Anugrah; Tran, Minh Xuan; Wang, Manxiang; Liu, Guicheng; Lee, Joong Kee
Abstract : A polar interlayer is introduced to TiO2 photoanodes as a novel strategy to improve the performance of fibre-shaped dye-sensitized solar cells. Abstract : A novel strategy to improve the performance of fibre-shaped dye-sensitized solar cells (FDSSCs) has been successfully implemented using a polar polymer interlayer made of poly(2-ethyl-2-oxazoline) (PEOx). The inclusion of the PEOx interlayer reduces the typical defect sites and interband trap sites that exist on the TiO2 -nanotube-based photoanode of the FDSSC. A local built-in electric field, induced by the interfacial intrinsic polarity of the PEOx interlayer, promotes facile photogenerated charge injection/extraction kinetics at the TiO2 /dye interface. The negative polarity present on the bottom part of the PEOx chain exhibits an electronic doping-like behaviour, passivating the TiO2 defect sites and reducing trap-assisted recombination, while the positive polarity present on the top part of the PEOx chain provides dye-rich anchoring sites to improve the N719 dye adsorption loading on the TiO2 surface. The charge collection efficiency, short-circuit current density, open-circuit voltage, and fill factor of FDSSCs with the novel TiO2 @PEOx photoanodes are superior than those of FDSSCs with traditional TiO2 photoanodes, by approximately 16.94%, 8.57%, 14.08%, and 6.58%, respectively. Consequently, the power conversion efficiency (PCE) of the proposed FDSSC is considerably improved, reaching 11.22%. Thus, the PCE of the proposed FDSSC is improved by approximately 32.16% compared with that of the traditional FDSSC.